Morphological, biochemical and genetic diversity of cumin from Iranian provinces - Bahraminejad, Alireza (2011)
In order to assess the genetic diversity of cumin and determine the traits effective on seed yield and cumin-aldehyde production, forty nine cumin ecotypes which are sub-populations belonged to nine populations from different provinces of Iran were evaluated based on morphological and biochemical traits. Results indicated a significant variation for all the measured traits among and within populations derived from different provinces. Kerman and Esfahan populations showed the best performance based on the phenotypic data, while Yazd had almost the lowest levels of traits. Correlation analysis showed number of seed per umbel and umbel per plant had highest relationship with seed yield. Path analysis also demonstrated that number of umbel per plant and number of seed per umbel had the most direct effects on seed yield and were identified as the most effective factors on seed yield. Cumin aldehyde was mostly correlated by number of umbel per plant. The present study showed that different qualitative characteristics such as seeds with light color and without trichome and leaves without trichome, alternate and large pods of petiole tend to produce high seed yield. Pattern analysis of different populations based on first two main principal components categorized the measured genotypes in to three groups: Pars, Northern_Khorasan, Golestan, Semnan and Yazd (Group1), Southern_Khorasan and Khorasan_Razavi (Group2) Kerman and Esfahan (Group3), where the third group are high yielding genotypes with different genetic background can be advised for cultivation and used in breeding programs. So the available genetic diversity among the Iranian cumin populations can be utilized to produce high yielding population of cumin. Moreover the phenotypic diversity as well as molecular variability among the populations, a significant variation was seen within the populations. It proves that during the years so many variations due to sampling and also cross pollination as well as crossing over produce different ecotypes within each population some of the populations such as Kerman have shown more variability within the population. It can be due to higher evolution speed as compared to other populations. Therefore, there is a high potential for cumin breeding in Iran and introducing these ecotypes to other countries. Cumin ecotypes showed different variation for the measured traits, the highest variation belonged to cumin-aldehyde. As these view Kerman and Esfahan populations had the best performance on cumin-aldehyde. Correlation analysis showed number of seed per umbel and umbel per plant had highest relationship with seed yield. Path analysis also demonstrated that number of umbel per plant and number of seed per umbel had the most direct effects on seed yield and were identified as the most effective factors on seed yield. Cumin aldehyde was mostly correlated by number of umbel per plant. The present study showed that different qualitative characteristics such as seeds with light color and without trichome and leaves without trichome, alternate and large pods of petiole tend to produce high seed yield. Evaluation of molecular variance using three joint molecular markers and phylogenic relationship of ecotypes was done for the first time. Within population variance showed the highest proportion of variation, the ecotypes in each population were different. AFLP markers showed more polymorphism than the other markers (RAPD and SSR). The highest PIC value belonged to E+AGT (0.66). Since this crop is cross pollinated and SSR is a codominat marker and AFLP has higher efficiency for assessing the polymorphism, using of SSR as well as AFLP can increase the impact of genetic survey. If genetic diversity is done based on a good coverage of AFLP & SSR markers in genome then the extreme genotypes based on distance can be chosen for hybrid production. Totally, based on all molecular markers clustering showed Yazd population has the biggest distance from the other populations, also Kerman and Khorasan populations which might have some ancestor had almost the close distance. Cluster of 49 cumin ecotypes, showed Zarand has arranged almost separately, it means that it may have different background than the others. The measured ecotypes were divided almost into five groups based on joint markers and comparison of phenotypic and molecular cluster therefore it can be confirmed that there is a good relation between the phenotypic and molecular clusters.